Sensitivity analysis for variational inclusions by Wiener-Hopf equation techniques. (1999) - Moudafi, Abdellatif; Noor, Muhammad Aslam
Abstract : In this paper, we extend the sensitivity analysis framework developed recently for variational inequalities by Noor and Yen to variational inclusions relying on Wiener-Hopf equation techniques. We prove the continuity and the Lipschitz continuity of the locally unique solution to parametric variational inclusions without assuming differentiability of the given data.